The (im)possibilities of dialogue across feminism and childhood scholarship and activism. Issue 2 (4th March 2017) - Twamley, Katherine; Rosen, Rachel; Mayall, Berry
Abstract : The relations between those positioned as women and as children, and the political and intellectual consequences of how we conceptualise these connections, has received only scant attention. In this article we describe a symposium and on-going project which aim to bring together community-based and academic scholars to debate the intersections and perceived antagonisms between various forms of feminism and the politics of childhood. We trace how these intersections have been debated in the literature and outline the potential benefits and pitfalls of encouraging further connections between these fields. Drawing on our symposium experience, we also outline the challenges involved in bringing together academic and community-based scholars and activists, and consider the implications for similar future endeavours.